2012
DOI: 10.7322/jhgd.46356
|View full text |Cite
|
Sign up to set email alerts
|

Perfil De Crianças Dependentes De Tecnologia No Municipio De Ribeirão Preto-Sp

Abstract: Resumo:Estudo descritivo, exploratório, com abordagem quantitativa que objetivou caracterizar crianças dependentes de tecnologia, residentes em Ribeirão Preto -SP, com relação às condições de gestação e nascimento, origem das necessidades especiais de saúde e demandas de cuidados. Participaram 102 mães ou responsáveis. Os dados foram obtidos no período de janeiro a abril de 2011, mediante aplicação de formulário, durante visita domiciliar. Os resultados revelaram que 57% das crianças são do sexo masculino; a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
0
2
0
6
Order By: Relevance
“…A study to describe technology-dependent children living in the city of Ribeirão Preto, SP showed that 90.2% of them demand pharmaceutical care. The medicines most often used on a daily basis are anticonvulsants, antibiotics, reflux medication, nutritional supplements and vitamins, steroids and muscle relaxants (6) . As the demands of pharmaceutical care are frequent and require technical-scientific skills, this study was developed based on the following question: How do mothers experience the pharmaceutical care of their technology-dependent children?…”
Section: Introductionmentioning
confidence: 99%
“…A study to describe technology-dependent children living in the city of Ribeirão Preto, SP showed that 90.2% of them demand pharmaceutical care. The medicines most often used on a daily basis are anticonvulsants, antibiotics, reflux medication, nutritional supplements and vitamins, steroids and muscle relaxants (6) . As the demands of pharmaceutical care are frequent and require technical-scientific skills, this study was developed based on the following question: How do mothers experience the pharmaceutical care of their technology-dependent children?…”
Section: Introductionmentioning
confidence: 99%
“…An exploratory study with a qualitative approach was undertaken, based on the theoretical framework of medical anthropology and the narrative method. The participants were twelve mothers of technology-dependent children, intentionally selected based on a sample of 102 mothers ( 11 ) . The 102 mothers were identified by an active search in the city between October and December 2010, who participated in the first phase of the doctoral dissertation.…”
Section: Methodsmentioning
confidence: 99%
“…Todavia, muitas dessas crianças, mesmo sobrevivendo, passaram a evoluir com problemas crônicos, que influenciaram de forma permanente em seu crescimento e desenvolvimento, por serem frágeis clinicamente e socialmente suscetíveis. [1][2][3] Os problemas crônicos, também chamados de condições crônicas de saúde, atuam lentamente e são considerados multifatoriais, dependentes de hábitos de vida, de fatores ambientais e fisiológicos, e sofrem variações ao longo do tempo. Enquanto que, problemas agudos apresentam-se em um período curto e tendem a se autolimitar.…”
Section: Introductionunclassified